O-GlcNAcylation of glutaminase isoform KGA inhibits ferroptosis through activation of glutaminolysis in hepatoblastoma - Sijia Fang; Guoqing Zhu; Yi Xie; Miao Ding; Ni Zhen; Jiabei Zhu; Siwei Mao; Xiaochen Tang; Han Wu; Qi Zhang; Aijia Zhang; Xin Ni; et al. (Cell Death Discovery)
Abstract Hepatoblastoma (HB), the most common pediatric hepatic malignancy, exhibits an increasing incidence. Metabolism reprogramming represents a pivotal hallmark in the oncogenic transformation process, with glutamine emerging as a critical energy source for neoplastic cells, rivaling glucose. However, the mechanism by which glutamine is involved in the development of HB remains unclear. Our study identified glutamine metabolism as a crucial factor in the development of HB. The key enzyme of glutamine metabolism, kidney-type glutaminase (GLS1), is activated in HB and regulates cell proliferation. Mechanistically, the GLS1 subtype KGA, utilizing glutamate derived from glutaminolysis, enhances glutathione (GSH) synthesis, which in turn inhibits ferroptosis in HB cells. Importantly, the Thr563 residue of KGA undergoes O-GlcNAcylation, enhancing enzyme activity and stability, accelerating glutaminolysis, and promoting the proliferation of HB. This study demonstrated that enhanced glutaminolysis, driven by GLS1, is crucial for the development of HB by inhibiting ferroptosis. The O-GlcNAcylation of KGA isoform ensures its stability and glutaminase function in HB cells, which can serve as a promising therapeutic target for KGA-mediated glutaminolysis in HB.